Enhanced thermal performance of phase change material-integrated fin-type heat sinks for high power electronics cooling. (March 2022) - Kim, Su Ho; Heu, Chang Sung; Mok, Jin Yong; Kang, Seok-Won; Kim, Dong Rip
Highlights: Phase change materials (PCMs) are embedded to the base plate of fin-type heat sinks. Thermal performance of heat sinks for high power electronics is investigated. PCM-integrated fin-type heat sinks have similar thermal resistances with conventional ones. PCM-integrated ones show excellent thermal capacitive effects in reduced cooling conditions. Abstract: We report the enhanced cooling performance of the phase change material (PCM)-integrated fin-type heat sink compared to conventional fin-type heat sink in high power electronics with two localized hot spots. The PCM-integrated fin-type heat sink is fabricated by embedding the phase change composite to the base plate of the heat sink. As an effort to effectively utilize thermal capacitive effects of PCM, the phase change composites with paraffin infiltrated to copper foams are deployed within circular hole arrays in the base plate, which is subsequently covered by a graphite sheet, to achieve excellent heat spreading characteristics. Considering the cooling environments of commercial high power electronics (insulated-gate bipolar transistor (IGBT)), thermal performance of the PCM-integrated and the conventional fin-type heat sinks is experimentally and numerically investigated upon the heating powers of 400∼800 W. While the PCM-integrated fin-type heat sinks have similar heat sink thermal resistance with the conventional fin-type heat sinks, the PCM-integrated fin-type heat sinks exhibit an effective time delay up to ∼27.3% of the hot-spot temperature rise until 80 ℃ of the heat sinks in reduced cooling conditions, showing the potential as an effective thermal managing platform of the PCM-integrated heat sinks in convection-limited cooling environments.